Envisioning Paths Towards Peacebuilding in Foreign Language Teacher Education - Aristizábal Cardona, Astrid Johana; Ortiz Medina, Janeth Maria (Íkala, Revista de Lenguaje y Cultura, 2023)
In a country struggling to emerge from the shadows of a relentless armed conflict, where media manipulation puts a stable reconciliation process at risk, foreign language educators are called on to act. This article presents the results of a study conducted with three foreign language students studying in one of the sites of a public university in the Department of Antioquia, Colombia, located in a region affected by cultural, structural, direct, and ecological violence. The study resorted to critical peace education and critical media literacy theories as well as to local contributions from a pedagogy of memory to foster critical consciousness about the armed conflict in Colombia. Data collection methods included a survey, recordings of class discussions, samples of students’ work, and individual and group interviews. Data showed that the participants reflected critically on the role of different war agents, increased their capacity to question media messages, recognized the relevance of including the victims’ voices, and created counter-texts to contest dominant narratives about the conflict. Findings confirm the urgent need to prepare future foreign language educators to respond to their learners’ harsh social realities and exert their agency to generate transformations. They also highlight the need to do more interdisciplinary work in ELT and to value the contributions of local knowledge that helps us both understand the dynamics of violence in our contexts and envision possibilities for peacebuilding in Colombia.